Atovaquone exerts its anticancer effect by inhibiting Na+/K+-ATPase ion transport in canine cancer cells - Yousef Alharbi (Veterinary World, 2023)
Background and Aim: New anticancer drugs are being developed to avoid the toxicity and chemoresistance of the currently available drugs. The Food and Drug Administration-approved anti-malarial drug atovaquone is known to act as a selective oxidative phosphorylation inhibitor in the mitochondria by competing with CO Q10 (mitochondrial complex II and III). This study aimed to investigate the effect of atovaquone by examining the Na+/K+-ATPase (NKA) activity in various canine cell lines.